Pengaruh Gaya Hidup Terhadap Perilaku Konsumtif Anak Nelayan di Desa Botubarani Kabupaten Bone Bolango: (The Effect of Lifestyle on the Consumptive Behavior of Fishermen's Children in Botubarani Village, Bone Bolango District) - Taan, Hapsawati; Gani, Imam Prawiranegara (e-Journal Ekonomi Bisnis dan Akuntansi, 2024)
The purpose of this study was to analyze the effect of lifestyle on the consumptive behavior of fishermen's children in Botubarani Village, Bone Bolango Regency. The research approach used is a quantitative research approach. The sample of this research is 100 respondents with purposive sampling technique. Data collection techniques using a questionnaire. The data analysis technique used is simple regression analysis. The results of this study show that there is a positive and significant influence of lifestyle on consumptive behavior. This is shown by the t count of 13,182 and the Sig. 0.000 < Î± 0.01, it can be stated that lifestyle has a significant effect on consumptive behavior. So it can be concluded that lifestyle has a contribution to the consumptive behavior of fishermen's children in determining their economic activities.